2017
DOI: 10.18869/acadpub.jnkums.9.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Investigating health literacy in patients with type2 diabets referring to the health houses of Chenaran in 2016

Abstract: (p=0.349), educational level (p=0.417), and age (p=0.451). Conclusion:This study indicated a low health literacy in patients with type 2 diabetes.Since low health literacy impedes perception of health information and medical instructions, therefore adopting effective strategies to promote this type of literacy seems to be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In the current study, there was no significant relationship between the average ages of people with HL in type 2 patients with T2D; these results are consistent with the review of Charoghchian Khorasani et al . [ 42 ] research. However, the results were inconsistent with the results of the studies done by Yeh et al .,[ 37 ] and Tahery et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, there was no significant relationship between the average ages of people with HL in type 2 patients with T2D; these results are consistent with the review of Charoghchian Khorasani et al . [ 42 ] research. However, the results were inconsistent with the results of the studies done by Yeh et al .,[ 37 ] and Tahery et al .…”
Section: Discussionmentioning
confidence: 99%
“…The results of the current study revealed that there is a significant relationship between monthly income and HL of patients with T2D, which is consistent with the results of studies done by Charoghchian Khorasani et al .,[ 42 ] Reisi et al .,[ 24 ] and Ansari et al . [ 30 ] This result was inconsistent with the results of the study conducted by Mashi et al .…”
Section: Discussionmentioning
confidence: 99%
“…These individuals have little knowledge about healthcare conditions and use less preventive services [14]. Studies show that health literacy is one of the factors influencing treatment adherence among patients with diabetes [15][16][17]. Limited health literacy is very common among patients with diabetes, which is associated with poor awareness and less understanding of diabetes as well as outcomes such as retinopathy and poor blood sugar control [18].…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Given the significant burden of chronic diseases, promoting the people's level of health literacy can play a decisive role in the prevention and treatment of these diseases and saving resources. [ 16 17 ]…”
Section: Introductionmentioning
confidence: 99%